Pengaruh Pembelajaran Mind Map Terhadap Hasil Belajar IPA Siswa Kelas VII SMP Negeri 1 Kaliwungu Kabupaten Semarang Semester Genap Tahun Pelajaran 2015/2016 - ALIFIAN CHANDRA ADI, ZADA, Dra. Hariyatmi, M.Si (2016)
This research is aimed to discover the effect of mind map learning toward the learning result science of seven grade students in SMP Negeri 1 Kaliwungu Semarang District in the second semester of 2015/2016 teching year. The research used true experiment method with posttest only control group design. Research population was class VII students.The sample data taken of three class with random sampling The data collected by final test (posttest) and documentation, data analysis which was used in the research was Independent Sample T-Test. Before the data were analyzed, prerequisite test was conducted, which were normality and homogeneity test. In mind map learning the results was obtained with average score was 75,19 and the control learning the average score was 72,03. Thus, it can be concluded that mind map learning can increase on learning result science of seven grade students in SMP Negeri 1 Kaliwungu Semarang District in the second semester of 2015/2016 teaching year.